Integrative microphysiological tissue systems of cancer metastasis to the liver. (June 2021) - Clark, Amanda M; Allbritton, Nancy L; Wells, Alan
Abstract: The liver is the most commonly involved organ in metastases from a wide variety of solid tumors. The use of biologically and cellularly complex liver tissue systems have shown that tumor cell behavior and therapeutic responses are modulated within the liver microenvironment and in ways distinct from the behaviors in the primary locations. These microphysiological systems have provided unexpected and powerful insights into the tumor cell biology of metastasis. However, neither the tumor nor the liver exist in an isolated tissue situation, having to function within a complete body and respond to systemic events as well as those in other organs. To examine the influence of one organ on the function of other tissues, microphysiological systems are being linked. Herein, we discuss extending this concept to tumor metastases by integrating complex models of the primary tumor with the liver metastatic environment. In addition, inflammatory organs and the immune system can be incorporated into these multi-organ systems to probe the effects on tumor behavior and cancer treatments.